渐开线齿轮反馈式稳健优化设计方法 - 周晓玲; 李刚; 汪中厚; 朱文敏; 耿直 (Jixie chuandong)
Aiming at the problems in the process of robust optimization design of involute gear,such as determining the dynamic load coefficient and multi-parameter nonlinear coupling,a method of dynamic load coefficient modified calculation is proposed.Through sovling the relative gain matrix between design parameter,the coupling relationship between the design parameter is reflected.Combining the optimization method of robust optimization design method,the feedback optimization design method of involute gear is put forward.This method not only improves the robustness of traditional optimization algorithm,but also reduces the difficulty to determine optimization parameters in the process of robust optimization design.By comparing the instance,gear parts,which designed by feedback robust optimization design method,can still maintain good quality of tooth contact and dynamic performance in the time variant situation.A new way of involute gear optimization design is provided.